Multiple-Locus Variable-Number Tandem-Repeat Analysis for Longitudinal Survey of Sources of Pseudomonas aeruginosa Infection in Cystic Fibrosis Patients - Vu-Thien, Hoang (American Society for Microbiology, 2007)
In order to identify the source of infection by Pseudomonas aeruginosa in patients with cystic fibrosis (CF), systematic genotyping of isolates is necessary. Multiple-locus variable-number tandem-repeat (VNTR) analysis (MLVA) was used to survey the sources of P. aeruginosa infections in a French (Paris, France) pediatric CF center. Between January 2004 and December 2006, 108 patients ages 2 to 21 years who were regularly monitored at the center provided sputum for culture. P. aeruginosa was detected in 46 children, 17 of whom had primary colonization. A total of 163 isolates were recovered. MLVA was improved from a previously published method by the addition of new, informative, and easily typeable markers. Upon genotyping with 15 VNTRs, a total of 39 lineages composed of indistinguishable or closely related isolates, were observed. One of them corresponds to “clone C,” which is widely distributed in Europe, and another corresponds to reference strain PA14. Six patients were colonized with two different strains, and the remaining 40 patients were colonized with a single strain. Strains from seven lineages were shared by at least two and up to four patients among a total of 20 patients. The study demonstrates that MLVA is an efficient, easy, and rapid molecular method for epidemiological surveillance for P. aeruginosa infection. The resulting data and strain genetic profiles can be queried on http://bacterial-genotyping.igmors.u-psud.fr.